Eco-friendly construction materials: Modified gypsum-containing bind - Asamatdinov Marat; Zhukov Alexey; Zhuk Peter; Bobrova Ekaterina; Medvedev Andrey (BIO Web of Conferences)
The use of gypsum-containing binders significantly expands both the raw material base and the possibilities of application of materials based on them. Clay-gypsum belongs to this group of binders. Clay-gypsum raw material and binder on its basis are local building materials. Binders based on clay gypsum have advantages under the following conditions: the remoteness of deposits of natural gypsum raw materials and the proximity of production from consumers. Clay gypsum is a natural formation of fine-grained crystalline gypsum, evenly mixed with clay or loam. The amount of gypsum varies from 50 to 95%. The aim of the research was the formation of scientific bases for obtaining clay-gypsum binder stabilized by its properties, as well as the development of optimized parameters for the production of this binder. As a result of research, the technological parameters of receiving clay-no-gypsum binder and modes of its thermal processing (firing) are optimized, and also the influence of technologies on the properties of clay-no-gypsum binder, which can be considered an analogue of binder received from natural gypsum raw material, is studied. It is established that at the age of 28 days of hardening, the compressive strength of clay-gypsum binder fired at the temperature of 250 oC reached 8.8–8.6 MPa, which at the accepted level of security allowed to obtain a binder of G-8 grade. The formation of soluble anhydrite did not exceed 1.5%.